Ensayos sobre Artes Visuales prácticas y discursos de los años '70 y '80 en Chile - Delpiano, Maria José, 1982- (Colección Artes visuales (LOM Ediciones), 2011)
Three winners essays of the "First contest of essays on visual arts" that deal with the cultural criticism that determined the artistic and pedagogic development of Chilean art during the 1970's and 1980's, particularly the performances of art collective "Yeguas del Apocalipsis (Francisco Casas and Pedro Lemebel) since 1988; the rupture and transformations generated in Chilean graphic art by artist Vilches and a revision of the local avant-garde movements.